2020
DOI: 10.1093/joc/jqaa017
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Persuasive Effects in Narrative Communication Research: A Meta-Analysis

Abstract: This meta-analysis builds on the broad and diverse research on the persuasive effects of narrative communication. Researchers have found that narratives are a particularly effective type of message that often has greater persuasive effects than non-narratives immediately after exposure. The present study meta-analyzes whether this greater persuasive power persists over time. Results are based on k1 = 14 studies with k2 = 51 effect sizes for immediate measurement (N = 2,834) and k2 = 66 effect sizes for delayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 58 publications
3
28
0
2
Order By: Relevance
“…Future primary studies should more frequently assess vaccination outcomes after a delay. As suggested in a meta-analysis by Oschatz and Marker (2020), narrative messages might have a stronger impact than non-narrative messages at delayed measurement.…”
Section: A Systematic Review Of Narrative Interventions Addressing Va...mentioning
confidence: 92%
“…Future primary studies should more frequently assess vaccination outcomes after a delay. As suggested in a meta-analysis by Oschatz and Marker (2020), narrative messages might have a stronger impact than non-narrative messages at delayed measurement.…”
Section: A Systematic Review Of Narrative Interventions Addressing Va...mentioning
confidence: 92%
“…Multiple theorists have argued that unique elements of narrative processing, including cognitive and emotional connections with characters and vivid imagining of story elements, could make narrative effects more likely to endure than other forms of messaging (e.g., Appel & Richter, 2007;Busselle & Bilandzic, 2008;Cohen, 2001;Green & Brock, 2002). The accumulated empirical evidence also supports this assertion: a meta-analysis of 14 studies with 51 effect size estimates at time 1 (immediately after exposure) and 66 estimates at time 2 (an average of two weeks later) found that narrative message effects were comparable across baseline (Cohen's d = .14, p = .003) and subsequent assessments (Cohen's d = .16, p = .001) (Oschatz & Marker, 2020). Third, in our own data, we found no evidence of differences in estimated effect sizes between respondents who completed the study in less than one hour versus those who completed the study over a longer time span.…”
Section: Methods Study Design Overviewmentioning
confidence: 85%
“…This issue became more relevant during the pandemic, when inperson trainings were less feasible and safe, leading to a decline in workplace anti-discrimination workshops 22 . Entertaining films and videos may help address this problem and function as highly scalable and impactful interventions 26,23 . Indeed, between April of 2020 and May of 2021 (i.e., during the pandemic), the documentary "Picture a Scientist" had a far-reaching international influence, with many organizational screenings and unique film views.…”
Section: Discussionmentioning
confidence: 99%
“…Media (e.g., films and television) has a unique potential to reach large audiences, and when carefully developed, can promote messages that inspire lasting change while entertaining viewers 23,24,25 . Thus, immersive and engaging videos may enhance online diversity interventions and ensure such trainings are widespread and scalable.…”
Section: Introductionmentioning
confidence: 99%